Relative Energy Deficiency in Sport (RED-S): A Systematic Overview of Mechanisms, Effects, and Clinical Implications - Fortuna, Milena; Hetnar , Paulina; Kiper, Sebastian; Toczek, Sławomir; Tomala, Magdalena; Jastrowicz-Chęć, Katarzyna; Koryszko, Klaudia; Pokrywka, Natalia; Suwała, Dawid; Polak, Marcelina (Quality in Sport, 2025)
Relative Energy Deficiency in Sport (RED-S) is a multifactorial condition resulting from low energy availability (LEA), where energy intake is insufficient to support physiological functions after accounting for exercise expenditure. Initially derived from the Female Athlete Triad, RED-S now encompasses a broader spectrum of health and performance consequences in both female and male athletes. LEA negatively impacts metabolic rate, menstrual and reproductive function, bone health, immunity, and cardiovascular and psychological well-being. Hormonal disruptions, including reduced levels of leptin, estrogen, testosterone, and thyroid hormones, contribute to impaired physiological adaptation and increased injury risk. Diagnosing RED-S requires a comprehensive assessment of medical history, nutrition, training, and psychological factors, often supported by tools like the RED-S Clinical Assessment Tool and DXA scanning (Dual-energy X-ray Absorptiometry). Treatment focuses on restoring energy balance through increased caloric intake, modified training, and psychological support. A multidisciplinary approach is essential for recovery, emphasizing education, early detection, and individualized care. Successful management leads not only to restored physical health but also to improved mental well-being and a healthier approach to sport.